Pengembangan Desa Digital di Desa Lawatan Kecamatan Dukuhturi Kabupaten Tegal - Nabilla Chesa Putri Hartono; Agus Widiyarta (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The adoption of decentralized and autonomous systems has created numerous opportunities for regional governments to drive development in various sectors, including rural governance. With the rapid advancement of technology, it is important for governments to keep up with the development of digital services. Lawatan Village is a prime example of a community that has successfully implemented the concept of a digital village. This research aims to investigate the development of a digital village in Lawatan Village, Dukuhturi District, Tegal Regency. The focus of the research is examined through the theory of successful elements of e-government development as identified by the Harvard JFK School of Government, consisting of support, capacity, and value. This research employs a qualitative, descriptive method in order to gain a comprehensive understanding of the digital village development in Lawatan. The findings indicate that the Lawatan Village Government has successfully implemented the concept of a digital village with the support of the government and sufficient resource management capacity. The development of a digital village has provided benefits to both the village.